Testing of dynamically substructured, base-isolated systems using adaptive control techniques. - Tu, J.Y.
Experimental techniques for testing dynamically substructured systems are currently receiving attention in a wide range of structural, aerospace and automotive engineering environments. Dynamic substructuring enables full-size, critical components to be physically tested within a laboratory (as physical substructures), while the remaining parts are simulated in real-time (as numerical substructures). High quality control is required to achieve synchronization of variables at the substructuring interfaces and to compensate for additional actuator system(s) dynamics, nonlinearities, uncertainties and time varying properties within the physical substructures. This paper presents the substructuring approach and associated controller designs for performance testing of an aseismic, base-isolation systems, which is comprised of roller-pendulum isolators and controllable, nonlinear magnetorheological dampers. Roller pendulum isolators are typically mounted between the protected structure and its foundation and have a fundamental period of oscillation far removed from the predominant periods of any earthquake. Such semi active damper systems can ensure safety and performance requirements, whereas the implementation of purely active systems can be problematic in this respect. A linear inverse dynamics compensation and an adaptive controller are tailored for the resulting nonlinear synchronization problem. Implementation results favourably compare the effectiveness of the adaptive substructuring method against a conventional shaking table technique. A 1.32 percent error resulted compared with the shaking table response. Ultimately, the accuracy of the substructuring method compared with the response of the shaking table is dependent upon the fidelity of the numerical substructure.
Keywords: Adaptive control; Minimal control synthesis algorithm; Dynamic substructuring; MR damper; Roller-pendulum system; Structural system testing